Skin lightening effect of seaweed gel formulation: An in vivo study - Ab. Hadi, Hazrina; Mohd Nor, N. (Malaysian Pharmaceutical Society, 2017)
INTRODUCTION: There are numerous skin lightening products out there that use harmful substances such as mercury and hydroquinone,. Therefore, seaweed gel formulation was formulated by using seaweed as the main ingredient to provide skin lightening effect to the skin as well as to provide moisture and improve skin conditions without greasy feels to the skin. OBJECTIVE: This study is to assess the skin lightening effect of seaweed gel formulation besides the safety of the formulation to the consumers. METHODS: A total of 15 healthy female subjects (19-24 years old) were selected according to skin condition, age and sun behavior. Melanin content, skin hydration, collagen intensity and skin elasticity were assessed using DermaLab Combo, Cortex Technology. All of the aforementioned assessments were done at mid volar area of the right forearm after applying the formulation at the respected area everyday for 28 days. The assessment was done once a week for 4 weeks. RESULTS: The seaweed gel formulation has significantly reduced the melanin content of the subjects, provides extra hydration to the stratum corneum as well as improving its collagen intensity. However, it does not significantly improve the skin elasticity. The reducing of melanin content shows significant difference after applying the formulation for 3 weeks. The hydration of stratum corneum improves after 1 week of applying the formulation, while collagen intensity increases after 3 weeks of applying the formulation. CONCLUSION: Seaweed gel formulation provides skin lightening effect as well as improves hydration and collagen intensity of the skin.